ANALISIS YURIDIS TERHADAP SISTEM PEMILIHAN KEPALA DESA TERKAIT MONEY POLITIC ( Studi Kasus Di Desa Pucung, Kecamatan Kismantoro, Kabupaten Wonogiri ) - Saidah, Siwi Ellis; Cahya, Fafa Nur; Wijayanti, Sofia Esti (Universitas Muhammadiyah Ponorogo, 2018)
In the village election system there is always a political problem. In the election of the village head the seizure of power is very natural. In order to gain a power the candidates of the village head justified various ways to win the election result of the village head. It is intended that each candidate of the village head can fulfill his wish to occupy the highest position at the village level.This research has purpose to know how the implementation of village head election system in Pucung Village, Kismantoro Subdistrict, Wonogiri Regency whether the village head election system refers to Law number 6 year 2014 about Village. From the results of the research we get that the village head election system, in Pucung Village, Kismantoro Subdistrict, Wonogiri Regency there are some violations that are not realized especially by the village community such as money politics and campaign that precedes the start line because it has become the culture of the village community.Violations contained in the village head election system, in Pucung Village, Kismantoro Sub-district, Wonogiri District due to lack of public knowledge about Law number 6 of 2014 on the Village is due to the low education of the village community.